2016
DOI: 10.1159/000446708
|View full text |Cite
|
Sign up to set email alerts
|

Poor Agreement between Predictive Equations of Energy Expenditure and Measured Energy Expenditure in Critically Ill Acute Kidney Injury Patients

Abstract: Background: There are multiple equations for predicting resting energy expenditure (REE), but how accurate they are in severe acute kidney injury (AKI) patients is not clear. Our aim was to determine if predictive equations for estimated REE accurately reflect the requirements of AKI patients. Methods: We included in this prospective and observational study AKI patients AKIN-3 assessed by indirect calorimetry (IC). Bland-Altman, intraclass correlation coefficient and precision (percentagem of predicted values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 42 publications
3
31
0
2
Order By: Relevance
“…Our study found that the REE estimated by the Harris and Benedict formula [19] was signi cantly lower than that measured by IC. This nding corroborates the indication not to use this formula in critically-ill patients and in patients with AKI [11,14,20,21] and the need to propose a new equation for AKI on dialysis. This study aimed to develop and validate predictive equations for REE in severe AKI patients using a machine learning approach.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our study found that the REE estimated by the Harris and Benedict formula [19] was signi cantly lower than that measured by IC. This nding corroborates the indication not to use this formula in critically-ill patients and in patients with AKI [11,14,20,21] and the need to propose a new equation for AKI on dialysis. This study aimed to develop and validate predictive equations for REE in severe AKI patients using a machine learning approach.…”
Section: Discussionsupporting
confidence: 75%
“…Modi ed Penn state equation had the best precision, although the precision rate was only 41%. As a conclusion, none of these equations accurately estimated measured REE in severe AKI patients on dialysis and most of them underestimated energy needs [14]. Recently more sophisticated models that used machine learning were applied in clinical practices resulting and better predict models [15].…”
Section: Introductionmentioning
confidence: 96%
“…This finding corroborates the indication not to use this formula in critically-ill patients, 7,[16][17][18] and in patients with AKI. 19 The best way to assess the energy needs of critically-ill patients with AKI is by means of IC. 19 In the present study, REE increased as measured by IC on the fifth day of follow-up, compared to days 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…19 The best way to assess the energy needs of critically-ill patients with AKI is by means of IC. 19 In the present study, REE increased as measured by IC on the fifth day of follow-up, compared to days 2 and 3. However, this Significant increase was seen only in REE without normalization for weight.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many predictive equations exist for predicting resting energy expenditure (REE), but the accuracy of these equations for estimating caloric requirements of critically ill patients is unclear [7][8][9][10][11][12][13]. Goes et al evaluated if nine different standard predictive equations for energy expenditure could accurately re ect the energy requirements of critically ill, mechanically ventilated AKI patients [14]. There was low precision and poor agreement between measured and predicted REE by the Harris-Benedict (HB), Mi in, Ireton-Jones, Penn State, American College of Chest Physicians and Faisy equations.…”
Section: Introductionmentioning
confidence: 99%